2023
DOI: 10.3389/fmicb.2023.1223151
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring genetic variability of Giardia duodenalis and Enterocytozoon bieneusi in raw vegetables and fruits: implications for food safety and public health in Mozambique

Abstract: Giardia duodenalis and Enterocytozoon bieneusi are etiological agents of enteric diseases characterized by diarrhea that can progress to chronicity in humans, especially in children and in immunocompromised patients. This study aims to assess the genetic pattern of G. duodenalis and E. bieneusi detected in vegetables and fruits commercialized in Maputo markets, Mozambique and determine their public health importance. Eight study points were sampled: a farmer zone, a wholesale, four retail markets, and two supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…K has been found in wild rats (Leopoldamys edwardsi and Berylmys bowersi) [48]. Additionally, some of these genotypes were found on environmental surfaces and in vegetables and fruits [49]. The detection of these genotypes in horticultural products monitored in this study expands their host range and highlights their potential public health significance.…”
Section: Discussionmentioning
confidence: 64%
“…K has been found in wild rats (Leopoldamys edwardsi and Berylmys bowersi) [48]. Additionally, some of these genotypes were found on environmental surfaces and in vegetables and fruits [49]. The detection of these genotypes in horticultural products monitored in this study expands their host range and highlights their potential public health significance.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to E. coli, other species such as Shigella, Salmonella, Giardia duodenalis and Enterocytozoon bieneusi, are also common. [41,48,49] In this study, it was found that 80.3% of travelers did not consume uncooked meat, because based on the interview results, most of them were vegan or vegetarian. In addition, they also said that consuming uncooked meat or meat that is not cooked perfectly is dangerous for health, because the bacteria inside it does not die.…”
Section: Related To Traveler's Diarrheamentioning
confidence: 69%
“…Furthermore, other enteric pathogens, such as Vibrio cholerae, Cryptosporidium, and Giardia lamblia, are frequently reported in waterborne and foodborne outbreaks in many Sub-Saharan African countries [81,82].…”
Section: Main Foodborne Pathogensmentioning
confidence: 99%